A Microanalysis of Employee Retention Strategies: The Case of Selected Convenience Stores and Their Practices - Ramadhan, Ramadhan; Hermanto, Cahyo; Tay, En; Hamdani, Mohammad (Electronic, Business, Management and Technology Journal, 2023)
The study examines the complexities of data management in a Bandung-based garment industry, where each division analyzes transactional flow data using Google Spreadsheets. Nevertheless, the precision of the transactional flow data throughout the organization is compromised due to inconsistencies emerging from uncorrected modifications in controlled data. In order to resolve this problem, it is essential to construct a data warehouse system along with visually attractive data visualization using Tableau dashboards. Integrating these systems aims to provide users with the relevant information required for efficient decision-making. The project aims to enhance business intelligence operations within the garment firm by creating a sophisticated information system that combines inventory accuracy, data warehousing, and visualization approaches. The project aims to improve data accuracy, simplify data management processes, and provide stakeholders with complete insights into corporate operations through carefully examining and applying these systems. The study's primary objective is to provide significant insights that can enhance the optimization of inventory information systems and business intelligence techniques in the garment industry. This condition will ultimately lead to improved efficiency and strategic decision-making abilities.